Efficacy, tolerability and acceptability of topical regimens containing the prebiotic Biolin in children suffering from atopic dermatitis. - Antão, H.S.; Passerini, E.; Guimarães, J.P.; Saldanha, J.; Coelho, J.D.; Fortunato, M. (European Journal of Pediatric Dermatology, 2017)
Prebiotics have the potential to correct skin dysbiosis and contribute to the improvement of atopic dermatitis (AD) when incorporated in topical moisturizers and emollients. Biolin is a combination of two prebiotics, alpha-glucan-oligosaccaride and inulin. This is the first study to test Biolin containing creams in AD in children. The study is aimed at assessing the efficacy, tolerability, acceptability and effects on quality of life of three Biolin containing topical creams (face cream, body wash cream and moisturizing body cream) in children with AD. This is single center, open label study, carried for 8 weeks in parallel subgroups of children aged 0-3 years with mild to moderate AD (SCORAD<35). Face and body wash creams were tested for 56 consecutive days in a subgroup of 30 subjects and the moisturizing body cream in the other 30 subjects’ subgroup. SCORAD indexes, xerosis, erythema and edema were assessed at the 4 study visits. Parents’ assessments were carried at 14, 28 and 56 days. SCORAD indexes significantly decreased for all creams at t28 and t56; average decrease ranged from 57.7% to 58.3%. Xerosis reductions were statistically significant for all creams at t56; xerosis improved in 96.6% to 100% of children. No erythema or edema emerged in children without these signs at baseline. Averages of parameters assessed by parents (pruritus, dryness, skin softness, quality of life and creams characteristics) were 8 (out of 10) or higher at the end of the study. The Biolin containing creams tested were beneficial and well tolerated in children aged 0-3 years with mild to moderate AD. The regimens were well accepted by parents and judged to improve both clinical manifestations and quality of life.